Methods for control over learning individual trajectory; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Mitsel A. A. Artur Aleksandrovich (Automation and informatization, economy and management of a company, 2015)
Title screen